2021
DOI: 10.3390/healthcare9010078
|View full text |Cite
|
Sign up to set email alerts
|

May Ibrutinib Have Activity in Respiratory Complications by SARS-CoV-2? Clinical Experience in a Patient with Chronic Lymphocytic Leukemia

Abstract: COVID-19 is affecting many countries all around the world. Unfortunately, no treatment has already been approved for the management of patients infected by SARS-CoV-2. It seems that SARS-CoV-2 can induce the activation of an exaggerated immune response against itself according to different mechanisms that are not really well known. Inflammatory interleukins, such as IL-6 among others, play a central role in this uncontrolled immune response. There is a strong rational under ibrutinib use in in the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Acalabrutinib treatment similarly ameliorates LPS/galactosamine-induced infiltration of macrophages and reduces serum levels of MCP-1 in a mouse model of hepatic damage by inhibiting TLR4-induced NF-κB activation (Shaker et al, 2020). Interestingly, a number of case studies have reported the effects of ibrutinib or acalabrutinib on attenuating inflammatory cytokine and chemokine release, lung injury and respiratory failure in patients with severe COVID-19 (Lin et al, 2020;Rada et al, 2020;Scarfo et al, 2020;Treon et al, 2020;Alsuliman et al, 2021;Benner and Carson, 2021;Fiorcari et al, 2021;Molina-Cerrillo et al, 2021). Specifically, Roschewski et al (2020) found that acalabrutinib treatment improves oxygenation and reduces IL-6 production in monocytes of patients with severe COVID-19.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…Acalabrutinib treatment similarly ameliorates LPS/galactosamine-induced infiltration of macrophages and reduces serum levels of MCP-1 in a mouse model of hepatic damage by inhibiting TLR4-induced NF-κB activation (Shaker et al, 2020). Interestingly, a number of case studies have reported the effects of ibrutinib or acalabrutinib on attenuating inflammatory cytokine and chemokine release, lung injury and respiratory failure in patients with severe COVID-19 (Lin et al, 2020;Rada et al, 2020;Scarfo et al, 2020;Treon et al, 2020;Alsuliman et al, 2021;Benner and Carson, 2021;Fiorcari et al, 2021;Molina-Cerrillo et al, 2021). Specifically, Roschewski et al (2020) found that acalabrutinib treatment improves oxygenation and reduces IL-6 production in monocytes of patients with severe COVID-19.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…Emerging clinical evidence shows that both acalabrutinib and ibrutinib have protective effects against pulmonary injury, decreasing the duration of mechanical ventilation and mortality rate for hospitalized patients with severe COVID-19 (138)(139)(140)(141). The protective effects of BTK inhibitors have also been observed in CLL patients with COVID-19, as the hospitalization rate and duration for severe COVID-19 is lower and shorter for CLL patients on ibrutinib versus those on other regimens or off treatment (142,(144)(145)(146).…”
Section: Covid-19 Sepsis and Other Infectious And Inflammatory Diseasesmentioning
confidence: 99%
“…Thus, there is a link between inflammation, immunity, angiotensin-converting enzyme 2, and cardiovascular damage. Systemic disease triggered by SARS-CoV-2 infection is primarily due to an exaggerated and inadequate immune response ( 13 ). The inflammatory response triggered by the virus is involved in increasing the production of proinflammatory cytokines, including TNFα, IL-1 and IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic cells contribute to increased VEGF production, which stimulates angiogenesis, and increases T-cell differentiation to Th17 cells and Tregs, as well as B-cell activation. This inflammatory process causes damage to various organs and tissues ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation